Application of diaphragm crurotomy by A.G. Savinykh at the reconstruction of oesophagealintestinal anastomosis after gastrectomy - N. E. Kurtseitov; G. T. Dambaev; A. P. Koshel; A. N. Vusik; M. M. Solovyov (Acta Biomedica Scientifica, 2015)
We report the analysis of the results forming esophageal-jejunal anastomosis in 19 patients with postgastrectomy syndrome after radical treatment of gastric cancer. Diaphragm crurotomy technically facilitates the formation of the anastomosis. The results of a comprehensive survey show that the healing of the esophageal-intestinal anastomosis is held by the type of primary tension in 16 (84,2%) operated patients, and in the late postoperative period shows no sign of stenosis of the anastomotic ring and the last remains elastic, performing closing function. Up to 1 year after surgery the overall quality of life in patients increased on average by 7,5% and amounted to 112,6 ± 5,1 points. Three years after surgery index tended to increase, reaching an average of 120,2 ± 4,1 points.